DNA-damage foci to detect and characterize DNA repair alterations in children treated for pediatric malignancies. - Nadine Schuler (Public Library of Science (PLoS), 2014)
Purpose In children diagnosed with cancer, we evaluated the DNA damage foci approach to identify patients with double-strand break (DSB) repair deficiencies, who may overreact to DNA-damaging radio- and chemotherapy. In one patient with Fanconi anemia (FA) suffering relapsing squamous cell carcinomas of the oral cavity we also characterized the repair defect in biopsies of skin, mucosa and tumor. Methods and materials In children with histologically confirmed tumors or leukemias and healthy control-children DSB repair was investigated by counting γH2AX-, 53BP1- and pATM-foci in blood lymphocytes at defined time points after ex-vivo irradiation. This DSB repair capacity was correlated with treatment-related normal-tissue responses. For the FA patient the defective repair was also characterized in tissue biopsies by analyzing DNA damage response proteins by light and electron microscopy. Results Between tumor-children and healthy control-children we observed significant differences in mean DSB repair capacity, suggesting that childhood cancer is based on genetic alterations affecting DNA repair. Only 1 out of 4 patients with grade-4 normal-tissue toxicities revealed an impaired DSB repair capacity. The defective DNA repair in FA patient was verified in irradiated blood lymphocytes as well as in non-irradiated mucosa and skin biopsies leading to an excessive accumulation of heterochromatin-associated DSBs in rapidly cycling cells. Conclusions Analyzing human tissues we show that DSB repair alterations predispose to cancer formation at younger ages and affect the susceptibility to normal-tissue toxicities. DNA damage foci analysis of blood and tissue samples allows one to detect and characterize DSB repair deficiencies and enables identification of patients at risk for high-grade toxicities. However, not all treatment-associated normal-tissue toxicities can be explained by DSB repair deficiencies.